Impact of COVID-19 on Health Status and Management of Patients with CNS Demyelinating Diseases: A Single-Center Study - Aueaphatthanawong, Kamonchanok; Sangsai, Onpawee (Siriraj Medical Journal, 2024)
Objective: Study the effects of COVID-19 on health status and alterations in managing patients with CNS-IDDs. Materials and Methods: A questionnaire-based approach was commenced at the MS and Related Disorders Clinic at Siriraj Hospital in Thailand from March 2021 to December 2021. The data obtained from the questionnaire was subjected to statistical analysis. Results: The study comprised 92 patients with CNS-IDDs, with 72.8% female and a mean age of 44.6±14.0 years. Overall, 67.4% of patients were vaccinated following Thai National guidelines. Only two patients were confirmed to have contracted COVID-19 infection. The most common treatment administered in the 92 CNS-IDD patients was Azathioprine (39.1%), prednisolone (32.6%), then 14.1% each in MMF and Rituximab. Sixty-one patients (66.3%) reported no relapse in the past year and no statistically significant difference among the diseases. The mean self-rated quality of life (QoL) score was 8.0±1.9 before the COVID-19 pandemic then drastically decreasing to 5.4±2.4 during the pandemic period. Overall, 56.5% indicated at least some impact on physical well-being, and 69.6% reported challenges to psychological health. 16.3% postponed or canceled their appointments during the COVID-19 pandemic, and 8.3% transitioned from face-to-face meetings with doctors in the clinic to telemedicine or telephone follow-up. Conclusion: Our study revealed that patients with CNS-IDDs experienced no significant change in relapse and a low incidence of COVID-19 infection. During the pandemic, overall, patients' QoL decreased both physically and psychologically.